PEMANFAATAN GRACILARIA SP. SEBAGAI KOMODITAS UNGGULAN DI DESA KUPANG SEBAGAI DAERAH DEVISA RUMPUT LAUT - Rohma, Sofia Ainur; Jiwanti, Nia Soka; Zahra, Nafiesa; Nurhaliza, Yunita Dwi; Herawati, Jenny Dwi; Habiburrochman, Habiburrochman (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
The foreign trade or export sector has a significant impact on Indonesia's economic growth, especially East Java. One of the regencies that is considered to have contributed to increasing exports is Sidoarjo Regency with quite large potential for Gracilaria products. Based on the main issues and opportunities of Sidoarjo district, the research team focused on economic empowerment which was actualized through the Entrepreneurial Village action in the PPK Ormawa program. Based on the issues discovered by the people of Kupang Village, Jabon District, the PPK Ormawa UKM Penalaran team created various innovations in processed food products. The food products have high quality, high marketability, and compete on the market. The products are healthy noodles and meatballs. This has been realized through the "Grapovition" program hence the community is able to make processed seaweed products. Training was also provided in making attractive packaging and digital marketing or "Gracimarket". In addition, the community is also trained to sell and market the products at large local exhibitions directly, through the Marketing by Booth "Marboth" program. Lastly, the "Si Ruru" program is also provided to expand sales of seaweed and processed seaweed products. The innovation programs of community service and empowerment activities carried out in Kupang Village, Jabon Sidoarjo District aims to achieve and realize SDGs points 8, 9, 10 and 17. The PPK Ormawa team measures the program's sustainability at 95% from the benchmark of having a business house to produce processed red seaweed